Pemberdayaan Masyarakat Melalui Pengelolaan Objek Wisata di Desa Saham Kecamatan Sengah Temila Kabupataen Landak - Viany, Irena; Babaro, Elisabet Ilvania; Jessika, Angelina; Shella, Yusta Maisa (PT. Riset Press International, 2024)
Community empowerment in managing tourist attractions in Stock Village, Sengah Temila District, Landak Regency. One of the famous tourist attractions is Betang Panjang Stock and is known as a traditional Dayak Kanayant traditional house. In this house there are people selling handicrafts typical of the Dayak Kanayant tribe such as woven bags and hats, miniature longhouses and carved shields. However, currently sales are not running due to the lack of human resources who make these crafts. In this case, the importance of community empowerment by the government is to increase community participation in managing tourist attractions so that they continue to exist and become an attraction for visitors. The main aim of the research is to analyze community empowerment efforts in managing the potential of local tourist attractions. This research uses a data collection method, namely by reviewing journals, news, books, statutory regulations and other documents. The research results show that community empowerment is a key factor in optimizing tourism potential in Stock Village. Various training and coaching programs have been implemented to improve community skills and knowledge regarding tourism destination management. Apart from that, the existence of partnerships between local governments, non-governmental organizations and local business actors also supports the effectiveness of empowerment.